The mystical Bektashi Order: The founder, growth and core of its teachings - Shehu, Fatmir Mehdi (Sultanbeyli Belediyesi And Istanbul University, 2012)
Throughout the history of Islamic Civilisation, many Muslim intellectuals have been a prey of the doctrines and principles propagated by the followers of different mystical orders in general, and the BektÉshÊ Order in particular. The BektÉshÊ Order, which can be categorised as a mystical order deviating from the core of Islamic teachings, has through its decrees and teachings affected the harts of many lay Muslims as well as intellectuals. This order has created many obstacles and problems for those who were eager to understand the real meaning of the Islamic teachings as conveyed by the Holy Qur’Én and the Sunnah of Prophet MuÍammad (p.b.u.h.). Many Muslim intellectuals have attempted to bring this order back to the core of Islamic teachings, but have failed as this order has been very active and developing very fast since many of its followers were involved in the politics of the Ottoman state. This article attempts to examine the emergence, growth as well as the most important teachings of this Order.